Factors Influencing Corporate Environmental Disclosures1. (5th March 2013) - Wegener, Matt; Elayan, Fayez A.; Felton, Sandra; Li, Jingyu
Abstract We investigate the effectiveness of the Carbon Disclosure Project (CDP), a not‐for‐profit organization that facilitates environmental disclosures of firms with institutional investors, thereby serving as a corporate governance mechanism for shareholders to influence the firm's environmental disclosures. We examine firm characteristics associated with firms' decisions to disclose carbon‐related information via the CDP for a sample of 319 Canadian firms over a four‐year period. In particular, we examine how firms' decisions to disclose via CDP are associated with shareholder activism, litigation risk, and the opportunity for low‐cost positive publicity once requested by the firms' "signatory" investors. Our results also show that management's decision to release climate change data is associated with domestic, but not foreign, signatory investors. We also find that disclosing firms tend to be those from lower polluting industries with less exposure to litigation risk. This suggests that this new form of coordinated shareholder activism may not be successful at altering the behavior of firms that are heavier polluters.